1998
DOI: 10.1016/s1010-7940(98)00092-x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic saphenous vein harvesting versus ‘open’ technique. A prospective study

Abstract: Endoscopic saphenous vein harvesting allows improved aesthetic aspect, less postoperative discomfort, with an increased time in harvesting in the beginning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 8 publications
1
17
0
6
Order By: Relevance
“…Overall, 22 of the studies reported the incidence of post-operative haematoma [4][5][6][15][16][17][18][19][20][21][22][23][24][25][26][28][29][30][31][32][33]37], with seven of these showing a statistically significant reduction in the MIVH as compared to the CVH group. Eleven of the studies were randomised [4][5][6][15][16][17][18][19][20][21][22], with metaanalysis of these calculating an incidence of haematoma of 53/676 (8%) in MIVH and 93/610 (15%) in CVH groups, with an odds ratio (OR) of 0.43 and confidence interval (CI) of 0.23-0.79, suggesting that this difference is statistically significant.…”
Section: Meta-analysis Of Haematoma Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 22 of the studies reported the incidence of post-operative haematoma [4][5][6][15][16][17][18][19][20][21][22][23][24][25][26][28][29][30][31][32][33]37], with seven of these showing a statistically significant reduction in the MIVH as compared to the CVH group. Eleven of the studies were randomised [4][5][6][15][16][17][18][19][20][21][22], with metaanalysis of these calculating an incidence of haematoma of 53/676 (8%) in MIVH and 93/610 (15%) in CVH groups, with an odds ratio (OR) of 0.43 and confidence interval (CI) of 0.23-0.79, suggesting that this difference is statistically significant.…”
Section: Meta-analysis Of Haematoma Resultsmentioning
confidence: 99%
“…Eleven of the studies were randomised [4][5][6][15][16][17][18][19][20][21][22], with metaanalysis of these calculating an incidence of haematoma of 53/676 (8%) in MIVH and 93/610 (15%) in CVH groups, with an odds ratio (OR) of 0.43 and confidence interval (CI) of 0.23-0.79, suggesting that this difference is statistically significant. When considering 12 studies that were fully matched for the patient criteria previously mentioned [4][5][6]15,16,18,19,[21][22][23]32,33], these results were reproduced, with an incidence of haematoma of 50/840 (5%) with MIVH as compared to 88/764 (11%) with CVH (OR 0.46, CI 0.23-0.92).…”
Section: Meta-analysis Of Haematoma Resultsmentioning
confidence: 99%
“…A dor foi classificada em intensa, quando necessitava de analgésicos parenterais; moderada: quando era aliviada com analgésicos via oral; leve quando estava presente durante o esforço físico e era aliviada com repouso, não necessitando de medicações e ausente (20) .…”
Section: Dissecção Da Veia Safena Magnaunclassified
“…The incidence of saphenous vein harvest site infection is reported to be between 1% and 24% in the literature. [3][4][5][6] Very little has been discussed about the morbidities associated with great saphenous vein harvest site infection (GSVHSI) following CABG. These complications very rarely require major surgical intervention, and are disturbing, both to the patient and to the treating surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…51 Now newer techniques utilizing minimally invasive endoscopic harvesting are in vogue and are being used in many centers. 35,[52][53][54] Minimally invasive techniques using endoscopic and nonendoscopic instruments to reduce surgical incisions and improve the visibility of the SV have been in use since 1996. 55 There is a reduction in trauma to tissues, reduction in injuries to the cutaneous vessels, and a reduction in postoperative infections.…”
mentioning
confidence: 99%